A Survey of Key Negotiation and Authentication Systems in WSNs - Tehseen, Mohammad; Javed, Huma; Hussain Shah, Ishtiaq; Ahmed, Sheeraz (EAI Endorsed Transactions on Energy Web, 2018)
Wireless Sensor Networks (WSNs) is a type of adhoc network that is use to sense some phenomena with the help of sensor nodes. The nodes have scarce resources like power, storage, processing power, sensing and communication. Now a day WSNs are helping as a main constituting component for variety of applications like intelligence gathering, battle field monitoring, pollution mapping, smart cities, smart homes and health care monitoring systems etc. To make such system a reality and work with reliability, data security needs a lot of attention to be handled properly. Due to scarce resources in WSNs, implementation of proper security technique is not quite simple rather it is a challenging task to accomplish. Huge number of security algorithms have been proposed for WSNs, but among them network wide master key based security systems are more appropriate due to less overhead in establishing a secure channel. In this survey different security solution such as LEAP, BROSK, Spins, C & R, Light Weight Authentication Systems and ECC are investigated to study the impact of physical attack on them.
Keywords: Wireless sensor networks; Elliptic Curve Cryptography; Symmetric and Asymmetric Cryptography